1981
DOI: 10.2307/1165995
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Sequences within and between Concepts

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
173
0
7

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(189 citation statements)
references
References 68 publications
9
173
0
7
Order By: Relevance
“…Earlier studies reported that Western children failed problems akin to our crucial tasks. For example, 5-yolds prefer to draw a token from a set containing 4 winning tokens and 4 losing token rather than from a set containing 2 winning tokens and 1 losing token (22). Compared with most previous problems, our tasks involved a larger number of tokens (e.g., 60 tokens in task Cright vs. 11 tokens in the above example), and a greater difference between proportions (e.g., 3:1 and 1:3 in task C-right vs. 2:1 and 4:4 in the above example).…”
Section: Study 2 Quantity Vs Proportionmentioning
confidence: 99%
“…Earlier studies reported that Western children failed problems akin to our crucial tasks. For example, 5-yolds prefer to draw a token from a set containing 4 winning tokens and 4 losing token rather than from a set containing 2 winning tokens and 1 losing token (22). Compared with most previous problems, our tasks involved a larger number of tokens (e.g., 60 tokens in task Cright vs. 11 tokens in the above example), and a greater difference between proportions (e.g., 3:1 and 1:3 in task C-right vs. 2:1 and 4:4 in the above example).…”
Section: Study 2 Quantity Vs Proportionmentioning
confidence: 99%
“…Included in the developmental changes that occur in the first 18 years or so is a tremendous increase in domain-general and domain-specific knowledge (e.g., Chi, 1978;Chi & Koeske, 1983), the ability to generate several potential solutions to a problem (e.g., Kuhn & Phelps, 1982), the ability to ignore irrelevant problem information (e.g., Halpern, 1989), the ability to think about more than one dimension of the problem simultaneously (e.g., Ferretti, et al, 1985;Inhelder & Piaget, 1958;Siegler, 1976Siegler, , 1981, and the ability to think about relationships among events in a bidirectional way (e.g., Inhelder & Piaget, 1958;Surber & Gzesh, 1984). Surber and Gzesh (1984) investigated the ability of both children and adults to solve scale-balance problems, using subjects whose ages averaged about 5, 8, 11, or 14 years, or college aged (no average age was given for the college students).…”
Section: Development Of Problem Solving Abilitymentioning
confidence: 99%
“…At present the best methodology of assessing conservation and several related abilities has been introduced by Siegler (1981; is correct on conservation tasks too, but more difficult and rarely used (Siegler, 1981). …”
Section: Issues With Conservationmentioning
confidence: 99%